IbM. KELOMPOK INDUSTRI KECIL PETANI JAMUR TIRAM DESA MANGIS KEC. LAWANG KAB. MALANG - Hasan, Khojanah; Bahri, Syamsul; Zulkifli, Zulkifli (DINAMIKA DOTCOM, 2016)
Among the many types of mushrooms, which currently has a good prospect is the kind of White Oyster Mushroom (Pleuratus ostreatus sp) which is also called wood fungus, because it grows on media decayed wood or sawdust. Oyster Mushrooms have very high nutrient content and includes food that is safe to be consumed by humans. Desa Manggis Subdistrict Lawang Malang is an area that many people cultivate oyster mushrooms, approximately 2-6 years before only as a laborer. Most people depend on the type of business, business karana is considered particularly help raise revenue than first job as a laborer. In the village of Manggis are 2 partners as coordinator of oyster mushroom farmers cultivating more. Daily average of 1,000 Â± able to work with labor baglog 5 to 8 people / day, while the order is very high and limited production. This is because the packing bag log is done manually and also the lack of knowledge about partner management, marketing and accounting. The results of the activities IbM conducted by Tim proposer has provided alternative solutions to some of the problems faced by the partners, including: the provision of appropriate technology ie pressing machine bag logs, training and assistance: the use of production machines, the importance of organizational structure, effective communication, and manufacturing simple bookkeeping. After getting this program, partners are already better than before their training and are expected to develop in parallel with its business and the other oyster mushroom farmers. Keywords: oyster mushroom farmer, bag logs, training, mentoring and appropriate technology.